Investment Attractiveness of Food Industries in Ukraine - YashchenkoL. О. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Effective investment is a factor for long-term company development. As enhancement of investment attractiveness is a required condition for economic growth and improvement of living standards, it needs to be on the agenda at government and company level. The article’s objective is to study investment attractiveness of food industries in Ukraine over 2012–2015. Investment attractiveness of food industries can be measured by indicators of liquidity, financial sustainability, and profit rate. Basically, food industries in Ukraine are attractive for investment, which is demonstrated by assessment of the financial indicators. The investment attractiveness worsened slightly in 2015 compared with 2014. The essential problems faced by food industries are shortage of internal funds and negative profit rate of all the activities, assets and own capital. Official statistical data and software package SPSS are used to build the dendrogram, allowing for dividing food industries by level of investment attractiveness into three groups: industries with high, medium and low level of investment attractiveness. It is found that meat industry is the one with the highest level of investment attractiveness. Also, investors should look positively at food-canning industry, oil and animal fat industry, flour-milling industry, starch and starch products industry, and other foods industry.